Perbedaan Mortalitas, Konversi Pakan, dan Performa Ayam Broiler pada Pola Kemitraan Antara Musim Hujan dan Kemarau - Paly, Muhammad Basir (Anoa: Journal of Animal Husbandry, 2025)
Partnership pattern broiler chicken production has contributed to chicken meat production, employment, and income of farmer households in rural areas. However, the challenge faced is the change of seasons which takes place twice a year which affects the production system. This study aims to evaluate differences in broiler chicken mortality, feed conversion (FCR) and Performance Index (IP) between the rainy and dry seasons. It was carried out in Gowa and Takalat Regencies from December to October 2022. Data was collected through surveys and interviews with 40 plasma farmers. The results showed that in the rainy season mortality was higher, FCR was not efficient, and IP performance was lower than in the dry season. I was concluded that broiler chicken maintenance in the rainy season has the potential to be detrimental to breeders. The implication of this research is that breeders need to minimize risks in the rainy season. It is recommended that breeders must be able to control the microclimate, especially humidity and wind speed which are ideal for broilers, maintain ration quality, and carry out fortification or the addition of certain substances to improve ration nutrition.